Microglia from patients with multiple sclerosis display a cell-autonomous immune activation state - Hyvärinen, Tanja; Tilvis, Johanna; Giudice, Luca; Tujula, Iisa; Nylund, Marjo; Ohtonen, Sohvi; Scoyni, Flavia; Jäntti, Henna; Virtanen, Lassi; Pihlava, Sara; Kattelus, Roosa; Skottman, Heli; et al. (BioMed Central, 2026)
Aberrant and sustained activation of microglia is implicated in the progression and severity of multiple sclerosis (MS). However, whether intrinsic alterations in microglial function impact the pathogenesis of this disease remains unclear. We conducted transcriptomic and functional analyses of microglia-like cells (iMGLs) differentiated from induced pluripotent stem cells (iPSCs) from patients with MS (pwMS) to answer this question. The pwMS showed increased innate immune cell activity via 18-kDa translocator protein positron emission tomography imaging. After confirming that the differentiated iMGLs transcriptional profile is determined by the microglial cell type, comparative studies were performed to identify the transcriptional and functional differences between iMGLs from pwMS and healthy controls. Importantly, MS iMGLs presented cell-autonomous differences in their regulation of inflammation, both in the basal state and following inflammatory lipopolysaccharide challenge. Through transcriptomic profiling, we showed that MS iMGLs display increased expression of genes upregulated in MS pathology. Furthermore, upregulated genes in MS iMGLs were associated with immune receptor activation, antigen presentation, and the complement system. MS iMGLs demonstrated transcriptional similarities to lesion-specific microglia in MS, marked by upregulation of immune-related genes and pathways, including those involved in antigen presentation. Finally, functional analyses indicated that the transcriptional changes in MS iMGLs corresponded with modulation of cytokine secretion and increased phagocytosis. Together, our results provide evidence of putative cell-autonomous microglial activation in pwMS and identify transcriptomic and functional changes that recapitulate the phenotypes observed in vivo in microglia from pwMS. These findings indicate that MS disease-specific iPSCs are valuable tools for studying disease-specific microglial activation in vitro and highlight microglia as potential therapeutic targets in MS.